Raising sanitary latrine use in rural Bangladesh: can BRAC play any role? - Hadi, Abdullahel; Nath, Samir R (BRAC Research and Evaluation Division (RED), 2019)
This study estimates the sanitation coverage and investigates impact of the participation in development program on the sanitation behavior in rural Bangladesh. Findings reveal that nearly a quarter of the study population has been using sanitary latrines though there are differences in use in terms of age, sex, education, occupation, land size and involvement with credit based development program. The multivariate analysis reveals that households involved with BRAC program are 3.66 times more likely to use sanitary latrine (p<.OI) than those who are socioeconomically similar with BRAC members but not involved in such program controlling for education and occupation of the household head. When other factors such as religion, ownership of land, housing condition, level of media exposure and the presence of BRAC programs are systematically added to the regression equation, the role of BRAC on sanitation behavior is still found significant. The study argues that social and behavioral aspects of the organized development program in rural Bangladesh can significantly increase safe sanitation practice in a traditional society.